Analisis Prediksi Kebangkrutan Dengan Menggunakan Metode Altman Z-Score Pada Perusahaan Sub Sektor Otomotif Yang Terdaftar di Bursa Efek Indonesia Pada Tahun 2019-2021 - Rohmatul Hasanah; Achmad Maqsudi (Journal of Creative Student Research, 2023)
The purpose of this study was to predict the financial difficulties of companies using the Altman Z-Score on companies in the automobile subindustry from 2019 to 2021. This research is qualitative research that uses descriptive methods. The data used in this study is secondary data, namely the financial statements of companies in the car subindustry from 2019 to 2021. The data analysis method used is the Altman Z-Score method by calculating five ratios, namely the ratio of Working Capital to Total Assets (X1), the ratio of Retained Earnings to Total Assets (X2), the ratio of EBIT to Total Assets (X3), the ratio of Market Value of Equity to Book Value of Total Liabilities (X4), and the ratio of Sales to Total Assets (X5). Research findings show that during the 2019-2021 period, there are four companies that are in safe zone conditions, namely PT. Garuda Metalindo Tbk, PT. Indospring Tbk, PT. Multi Prima Sejahtera, and PT. Congratulations. Two companies are in a gray zone condition, namely PT. Astra Internasional Tbk and PT. Astra Otoparts Tbk. Meanwhile, three companies are in crisis zone conditions, namely PT. Gajah Tunggal Tbk, PT. Indomobil Sukses Internasional Tbk, and PT. Prima Alloy Steel Universal Tbk. PT. Indo Kordsa Tbk, in 2019 was in a safe zone condition, in 2020 it was in a gray zone condition, and in 2021 it was in a safe zone condition. PT. Goodyear Indonesia Tbk, in 2019 was in a gray zone condition, in 2020 it was in a crisis zone condition, and in 2021 it was in a gray zone condition. While PT. Multistrada Arah Sarana Tbk, in 2019 was in a crisis zone condition, in 2020 it was in a gray zone condition, and in 2021 it was in a safe zone condition.